A TRANSITIVITY ANALYSIS OF AN EFL TEACHER TALK - Kelik Wachyudi; Shofura Zahrah Adn (Universitas Singaperbangsa Karawang, 2021)
The aim of this paper is to untangle how an English teacher in the classroom carries out the transitivity process. Based on this point of view, the research focuses on realizing the transitivity process by an English teacher in class. The methodology implemented for this study is a qualitative descriptive. The researchers consider the method is consistent with this research because it is naturally occurring. The results and discussion of this research are that the researcher met all forms of transitivity such as material processes (8), mental processes (9), verbal processes (7), relational processes (6), behavioral processes (2), and existential processes (5). Established along with the discussion of these determinations, the researchers found that the most astounding number was mental affection. What does it mean? The English teacher emphasizes that students promote their affection and thoughts when they act. The bottom line is that the English teacher focuses on mental processes. The teacher triggered students' affection and cognition to realize their perceptual experiences and desires, and et cetera.